PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. KARYA TAMA BAKTI MULIA KABUPATEN KAMPAR - Reni Puspita Sari; Marzolina -; Taufiqurrahman - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study was conducted at Tama PT.KaryaBaktiMulia Kampar District, with the aim to determine the effect of leadership and supervision either simultaneously or partially on work discipline employees at Tama PT.KaryaBaktiMulia Kampar district.Population of 110 persons and the number of samples is as many as 52 people. Which is based on the method of slovin. As an independent variable in this study is the leadership and supervision and the dependent variable is the discipline of work. While the data analysis techniques using multiple linear regression with the help of SPSS (Statistical Package for Social Science) version 18. Based on the results of the F test is known that the leadership and supervision simultaneously significant effect on employee discipline. While based on the results of the t test is known that the leadership and supervision of partially significant effect on employee discipline. Based on the test results obtained by the determination coefficient R Square value in the study, then this value will be changed to the shape percent. This means that the percentage contribution of variables influence the leadership and oversight of the work discipline of employees at Tama PT.KaryaBaktiMulia Kampar district. The recommendation that the authors propose for the company should be stressed sanctions and penalties should be more aware pimpinanan character, the nature of leadership should supervise its employees and workers to live more dispilin employees and employee performance will be better later.Keywords: work discipline, leadership, supervision